Expand and simplify the following: (x+2)(x+4)

1 answer

To expand and simplify the expression (x + 2)(x + 4), we need to use the distributive property.

First, distribute x to both terms in the second parenthesis:
x(x + 4) = x^2 + 4x

Next, distribute 2 to both terms in the second parenthesis:
2(x + 4) = 2x + 8

Now, we add the two expanded terms together:
(x + 2)(x + 4) = x^2 + 4x + 2x + 8

Combine like terms:
(x + 2)(x + 4) = x^2 + 6x + 8

Therefore, the simplified expression is: x^2 + 6x + 8.